Między obrazem a słowem – mediacyjny wymiar analizy materiałów ikonograficznych nacechowanych kulturowo na przykładzie studentów filologii romańskiej - Sujecka-Zając, Jolanta; Szymankiewicz, Krystyna (Neofilolog, 2026)
Developing personal and intercultural awareness and sensitivity is an inherent element of contemporary language education, while remaining a challenge in terms of the forms and methods of its implementation in language classes. The impulse for this analysis is the Council of Europe publication Images of Others: An Autobiography of Intercultural Encounters through Visual Media (AIEVM), (fr. Autobiographie de rencontres interculturelles par le biais des médias visuels 2013), in which, through guided reflection, the student carries out a written reflection regarding culturally significant iconographic material that they have chosen. This offers an opportunity for conducting intrapersonal mediation (Janowska, 2017), whose aim is not only to know and understand the Other, but above all one’s own Self and to develop higher levels of consciousness (Kielar, 2015). The analysed corpus will include selected statements from participants of the processes of language teaching/learning classes, held in the summer semester of 2024/2025 at the Institute of Romance Studies at the University of Warsaw. The aim of the study is to categorize manifestations of intrapersonal mediation in student work focused on interpreting an image related to cultural otherness, as well as to critically analyse the Autobiography... as a tool for intercultural reflection in terms of developing critical cultural (self-) awareness.